The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/app10072583
|View full text |Cite
|
Sign up to set email alerts
|

Crash Classification by Congestion Type for Highways

Abstract: Effective management of highway networks requires a thorough understanding of the conditions under which vehicular crashes occur. Such an understanding can and should inform related operational and resource allocation decisions. This paper presents an easily implementable methodology that can classify all reported crashes in terms of the operational conditions under which each crash occurred. The classification methodology uses link-based speed data. Unlike previous secondary collision identification schemes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Salek et al [ 19 ] presents a method for assessing the likelihood of freeway secondary crashes with Adaptive Signal Control Systems (ASCS) deployed on alternate routes. Song et al [ 20 ] present a methodology using link-based speed data to classify all reported crashes based on operational conditions, without prior identification of the cause. A case study on a 274 km section of I-40 revealed 12% of crashes in non-recurrent congestion, with 37% linked to unreported primary incidents, while the rest were classified as primary crashes in uncongested conditions (84%) or recurrent congestion (4%).…”
Section: Introductionmentioning
confidence: 99%
“…Salek et al [ 19 ] presents a method for assessing the likelihood of freeway secondary crashes with Adaptive Signal Control Systems (ASCS) deployed on alternate routes. Song et al [ 20 ] present a methodology using link-based speed data to classify all reported crashes based on operational conditions, without prior identification of the cause. A case study on a 274 km section of I-40 revealed 12% of crashes in non-recurrent congestion, with 37% linked to unreported primary incidents, while the rest were classified as primary crashes in uncongested conditions (84%) or recurrent congestion (4%).…”
Section: Introductionmentioning
confidence: 99%
“…The traffic scheme and the analysis of an intersection take into account elements of traffic, systematizing the whole process by synchronizing the signal with the control assembly of the traffic management system [12,13]. Thus, in order to create the simulation scenarios, additional direct simulation tools were used, including macro backgrounds, adjustment of directions and ground, and arrangement of intersections in order to render a real transport system reproduced with the defining elements imposed by legislation [14][15][16].…”
Section: Introduction To Traffic Flow Theorymentioning
confidence: 99%